IT project decisions: conclusions and recommendations for corporate practice. Issue 4 (2nd December 2019) - Idler, Boris David; Spang, Konrad
Abstract : Purpose: The purpose of this paper is to clarify the relevant determinants of IT project decision making and their relevance in corporate practice. Design/methodology/approach: The empiric analysis used in-depth expert interviews ( n =18) as method for data collection and qualitative content analysis using evaluative categories for analysis. Findings: Corporate practice is strongly influenced by descriptive decision making. There is only little use of normative decision models in decision making. In corporate practice little use is made of evaluations to analyze achieved project outputs and impacts to improve decision-making practice. This is the result of several evaluation barriers in organizations. Research limitations/implications: The sample is restricted to IT projects as the experts are responsible for IT project portfolio management. Also, an industry comparison is not included in the study. Practical implications: The analysis shows that IT project decision making in corporate practice should include results from descriptive decision theory into project decision processes in corporate practice. More effort should be made in challenging project input data which is relevant for project decision making. By systematically including evaluations for relevant projects, the deviations between planned and achieved project impacts offer valuable feedback for estimators and decision makers. Originality/value: The paper presents detailed analysis on decision variables and their relevance for IT project decision making in corporate practice. Critical aspects of decision making become clear, such as the aspects of evaluation barriers and the need to incorporate descriptive decision-making aspects into corporate decision processes.